Towards a Conceptualization and an Operationalization of the Construct of Employee Engagement - Iddagoda, Y.A.; Opatha, H.H.D.N.P.; Gunawardana, K.D. (Canadian Center of Science and Education, 2016)
Attached

Employees are generally considered as the most important resource needed for an organization to achieve its main goals. Realization of goals achievement heavily depends on the extent to which these employees are engaged in their jobs and their organization. Employee engagement is a factor that contributes positively to employee productivity and then organizational effectiveness. It reveals that a conceptual confusion exists with regard to the meaning of employee engagement owing to that the concept has been defined by different scholars in different ways and also that there are several associated terms such as job satisfaction, job involvement, work involvement, organizational commitment and organizational citizenship behavior which have been used in the literature, either synonymously or non-synonymously. Further a question arises to decide whether employee engagement is an attitude or a behavior. This paper seeks to provide a comprehensive conceptualization of employee engagement that results in formulating a working definition for research purposes involving the construct, and to explore its dimensions and elements for the purpose of measuring the construct.
Keywords: Conceptualization; Employee engagement; Operationalization